Communication skills in pharmacy practice : a practical guide for students and practitioners - Beardsley, Robert S.; Kimberlin, Carole L.; Tindall, William N. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2007)
The Fifth Edition of Communication Skills in Pharmacy Practice helps pharmacy and pharmacy technician students learn the principles, skills, and practices that are the foundation for clear communication and the essential development of trust between them and their future patients. This text's logical organization guides students from theory and basic principles to practical skills development to the application of those skills in everyday encounters. Sample dialogues show students how to effectively communicate and practical exercises fine tune their communication skills in dealing with a variety of sensitive situations that arise in pharmacy practice NEW TO THE FIFTH EDITION: New Pharmacy and Pharmacy Technician Instructor's Manuals available on the textbook's thePoint site help faculty administer and deliver their courses. New chapter on medication safety and communication skills (Chapter 9) offers strategies to reduce medication errors and protect patient safety. New chapter on electronic communication in healthcare (Chapter 13) provides guidelines to avoid common misunderstandings via email and the Internet. Expanded coverage of communication skills and interprofessional collaboration (Chapter 12) helps students learn how to effectively interact with other members of the healthcare team New photographs, illustrations, and tables visually engage students and enhance learning and retention of important concepts.
Patient-centered communication in pharmacy practice -- Principles and elements of interpersonal communication -- Nonverbal communication -- Barriers to communication -- Listening and empathic responding -- Assertiveness -- Interviewing and assessment -- Helping patients manage therapeutic regimens -- Medication safety and communication skills -- Strategies to meet specific needs -- Communicating with children about medicines -- Communication skills and interprofessional collaboration -- Electronic communication in health care -- Ethical behavior when communicating with patients.
Includes bibliographical references and index.
Keywords: Communication in pharmacy; Pharmacist and patient; Communication; Pharmacists; Professional-Patient Relations